Propuesta de un manual de responsabilidad social empresarial para empresas productoras y comercializadoras de café, caso de estudio Café “Indera” de la ciudad de Loja. - López Zongor, Janeth Marisol (2020)
The thesis entitled "Proposal for a manual on Corporate Social Responsibility for coffee producing and marketing companies, Case study Café Indera of the City of Loja" was carried out with the purpose of elaborating an instrument that allows introducing CSR guidelines into the organizational culture of the company, to generate an efficient administration, improve the relationship and performance with its employees and society in general. The research was supported by a theoretical framework in which there are bases to carry out the elaboration of the CSR manual, several concepts and international standards on the subject were reviewed, in particular the ISO 26000 Standard, established by the International Organization for Standardization; To this is added a methodology based on the identification of interest groups, to then prioritize them according to their influence, which facilitated the investigation based on internal interest groups: suppliers, employees and customers. In the development of the research work, different methods were used such as: the descriptive method that was used for the analysis of the data obtained in the application of the surveys, the deductive one was used at the time of carrying out the bibliographic review, the synthetic one allowed to specify the common characteristics of the population under study and with the analytical method, the parameters of the instruments for the preparation of the CSR manual were analyzed. In the same way, techniques such as: surveys, interviews with the interest groups of Indera coffee were applied, in order to know the level of knowledge and application regarding corporate social responsibility. The results present the interpretation and analysis of the diagnosis, the same that was carried out based on the survey that was applied to these interest groups, the general questions were analyzed in which it could be shown that 26% of the clients are clarify the concept of Social Responsibility. Only 18% of employees know the concept of this topic. Likewise, 20% of the suppliers have a defined concept. The questions based on the 7 topics of the ISO 26000 Standard were also analyzed, which were reflected in summary tables for greater understanding. The ISO 26000 Standard was carefully analyzed and the content that served as the basis for adapting and developing the manual was systematized. Based on all the aforementioned in the discussion, the manual is proposed by proposing a structure with valuable and important information to put these criteria into practice, additionally an annual operating plan was designed for the year 2021, as a tool to implement in practice the manual and a control sheet for compliance with it. Finally, it has been possible to conclude that half of the clients are not clear about the concept of Social Responsibility, in the same way it happens with the employees and suppliers who, for the most part, do not know this subject, due to the lack of knowledge and commitment of a company with society. With respect to the ISO 26000 standard indicators, both employees, clients and suppliers have a medium level of knowledge in Social Responsibility criteria due to the fact that there is no culture oriented towards it, and although there are points that are met, but it develops in isolation. Therefore, this proposal is made available to Café Indera as a strategy to improve its business image.